Numerical Simulation of Natural Convection Between Two Parallel Plates - Rosli, Aishah (Universiti Teknologi PETRONAS, 2011)
Free convection flow is present and significant in various engineering circumstances, such as the design of heat exchangers, nuclear reactors, and many chemical processes. It is also important in the application of cooling equipment. In this project, a two-dimensional numerical model is formulated to simulate the natural convection of air between two parallel plates using a computational fluid dynamics (CFD) code. Several different situations are modeled to observe the effects on the natural convection flow.